My molecular cuisine kit 28 recipes - Casor, Anne.; Lienard, Christine ([Boca Raton, FL] : CRC Press, 2012)
It's about taste, texture, mouthfeel, and, most importantly, satisfaction. Called'the science of deliciousness' by acclaimed cookbook author Harold McGee, molecular gastronomy is arguably the hottest cooking trend since, well, since cooking with fire became so popular. Top Chef fans have oohed and aahed over astounding culinary delights and puzzled over the revolutionary foam, gelee, and spherification techniques highlighted on the show.
Title from title page of the book
Keywords: Cooking; Molecular gastronomy